Contact Investigation Among Household Contacts of Drug-Resistant Tuberculosis Patients in Medan - Handan Rizky; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Taufik Ashar (Jurnal Impresi Indonesia, 2025)
Household contacts of Drug-Resistant Tuberculosis patients potential to develop latent tuberculosis infection (LTBI) or active tuberculosis (TB) infection. This research aims to determine the prevalence of LTBI and Pulmonary TB and the characteristic of household contact with Drug-Resistant Tuberculosis (DR-TB) patients. This is a descriptive analytical study using a cross-sectional approach in people aged > 18 years who have household contact with DR-TB patients whom confirmed by sputum GeneXpert and treated at Adam Malik Hospital Medan. The research subjects then underwent examinations including symptom anamnesis, chest X-ray, sputum GeneXpert, and IGRA blood test From 105 people who had household contact with DR-TB patients, the most common cases found were LTBI cases (55%), followed by uninfected cases (40%). Meanwhile, the only cases of Pulmonary TB found were Drug-Sensitive Pulmonary TB were 6 cases (5%) which are bacteriologically confirmed drug-Sensitive TB was 4 cases and clinically confirmed drug-sensitive TB was 2 cases. Majority of patients were in 18-30 year old group (30.5%), female (70%), high school graduates (61%), housewives (41%), normoweight (80%), no smoking habit (78%), no consuming alcohol (97%), and no comorbid diseases (87.5%). Based on contact duration, 70 people (67%) were found with > 5 hours and 35 patients (33%) with < 5 hours. In addition, the majority of samples (70%) did not sleep in the same room with MDR-TB patients.  LTBI cases were the most common cases found among household contact with DR-TB patients.